(untitled) (American Journal of Islam and Society, 2021)
The United States may be the most racially diverse and religiously pluralistic nation-state today. However, it is also arguably the most societally biased, one where many religious communities are frequently divided along distinct lines predicated upon race, color, ethnicity, and faith tradition. The sociohistorical displacement and dissemination of Islamic power away from indigenous African American Muslims to the newly disembarked post-1965 immigrant Muslims underscore the nascent religio-racial origins of how Islamic identity, membership, community, and consciousness within America has now become unusually conflated with race, culture, and ethnicity within our nation’s social imaginary. That is, what it contextually means to be a Muslim in the United States has now become a highly contested, problematic, and racialized category within American Islam—a segregated Islamic reality and existence that is being renegotiated and challenged by modern-day Black Muslims dissatisfied with their oppressed, marginalized and subaltern condition as Muslim Americans within the umma.